Common Fixed Point Results for Multivalued Mappings in Hausdorff Intuitionistic Fuzzy Metric Spaces - Azam, Akbar; Kanwal, Shazia (Communications in Mathematics and Applications, 2018)
The main objective of this paper is to derive common fixed points on a sequence contained in a closed ball for a family of multivalued mapping in a complete intuitionistic fuzzy metric space. Simple and different technique has been used. To give the strength of our result, an illustrative example is constructed.
Keywords: Fuzzy metric spaces; Intuitionistic fuzzy metric spaces; Fixed points; Common fixed points; Hausdorff metric spaces; Multivalued map